CONTEMPORARY ANGLO-AMERICAN BLURB AS ADAPTATION OF A CLASSICAL ENGLISH DETECTIVE - LEHEIDA, Alina; LEHEIDA, Dmytro (Linguistic and Conceptual Worldviews, 2022)
This paper is aimed at presenting a comprehensive multi-level analysis of the blurb as a component of an Anglo-American publication and created after a classical detective novel. Blurbs are conventionally placed on book covers (or on the Internet) describing the book content and strategically presenting the book to its potential audience. The multi-level model for comprehensive blurb analysis is pioneered, combining lexical, morphological, syntactic, graphic-visual and pragmatic levels of analysis. This study pursues to prove that blurbs are marked by their special communicative purpose and are inherently multi-functional (advertising, persuasive, influential) created with a view to persuade prospective audience to purchase the book. With respect to these blurbs are strategically equipped with various discursive and linguistic markers outlined in each of the levels of the model. At the structural level the structural divisions of the blurb invariant are investigated: the respective introduction, the central part and the final part. At the lexical level the appropriate lexical components of the introduction, central part and final part are analyzed. A set of corresponding standard lexical repertoires for each of these parts is established. At the morphological level the grammatical structures of each part are analyzed and described. At the syntactic level, the traditional syntax of each of the relevant parts is analysed. The graphical-visual level identifies the graphical and visual means that are most efficiently used by blurb creators to appeal to the audience. At the pragmatic level the pragmatic functions of the blurb are identified, which exercise the appropriate pragmatic impact on the reader. The study indicates that the process of making a blurb requires adherence to certain blurb-making laws and conventions.